Factors associated with dietary behaviour in kidney transplant recipients: a cross-sectional study - Fang, Jiaxin; Lin, Xiaohong; Wei, Changyun; Wang, Qianlu; Lin, Keke; Zhang, Shuping; Zhao, Peiyu; Li, Xiangru; Liu, Hongxia (Frontiers in Nutrition, 2025)
BackgroundDietary behaviour among kidney transplant recipients (KTRs) is a critical factor influencing long-term postoperative outcomes. However, research focusing on the dietary behaviour of KTRs remains limited. The aim of this study was to examine the dietary behaviour and explore the influencing factors of dietary behaviour in KTRs based on a health promotion model.MethodsThis was a cross-sectional study. A total of 289 KTRs from four hospitals were recruited from October 2022 to March 2023 by convenience sampling method. Participants completed a survey consisting of a general information questionnaire, the Dietary Self-management Ability Scale, the Perceived Dietary Behaviour Benefit and Barrier Questionnaire, the Self-Rating Depression Scale, and the Adapted Health Eating Cognitive Beliefs Questionnaire. The survey was administered both online and on-site. Data were analysed with Spearman’s correlation analysis and path analysis.ResultsDietary behaviour was at moderate level, with an index score of 78%. Depression (β = −0.207, p < 0.001), perceived behaviour benefits (β = 0.220, p < 0.001), perceived behaviour barriers (β = −0.234, p < 0.001), attitude (β = 0.135, p = 0.026), and social support (β = 0.166, p = 0.001) directly predicted dietary behaviour, while depression, attitude, and social support exhibited indirect effect on dietary behaviour.ConclusionMedical staff could help KTRs change their poor dietary attitude and negative mode, guide them to receive more social support and perceived benefits, reduce their perceived barriers. These positive shifts could ultimately facilitate the emergence of healthy dietary behaviour and enhancement of quality of life.